Overcoming Barriers to Climate Change Adaptation Implementation in Southern Africa - Duff, Lyndsey; Masters, Lesley (Book collections on Project MUSE., 2011)
Adapting to the impacts of climate change is one of the greatest challenges facing the African continent. Although initially couched as primarily an environmental challenge, its importance in the socio- economic development of the region has seen the prioritization of adaptation in the African common position at the United Nations Framework Convention on Climate Change (UNFCCC) climate change negotiations. This emphasis has resulted in a number of studies on the vulnerability of countries to climate change, including case studies detailing examples of adaptation in practice. Yet the understanding of the implementation of adaptation measures needs further nuance in its approach. This book goes beyond highlighting the importance of adaptation in supporting future socioeconomic development, to grappling with the challenges in implementing adaptation measures with the authors addressing some of the key obstacles facing the implementation of adaptation projects. In building an understanding of the barriers, and in unpacking the real implications for those leading adaptation efforts in Southern Africa, this book aims to not only bring to the fore elements that act as a constraint, but to further the discussion on how best to overcome these barriers in adapting to climate change.